Fused deposition 3D printing normal pressure liquid phase sintering silicon carbide ceramic and preparation method thereof

Through melt deposition 3D printing atmospheric liquid phase sintering technology, the problems of long processing cycles and high cost in the traditional ceramic preparation process are solved, and the high density and uniformity of silicon carbide ceramics are achieved, and its mechanical properties and thermal conductivity are enhanced.

CN119569459APending Publication Date: 2025-03-07SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411722287.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The traditional ceramic preparation process has problems of long processing cycles and high cost. Especially when manufacturing components with complex shapes or porous structures, the existing normal-pressure solid phase sintering methods cannot effectively improve the density and uniformity of the material, resulting in insufficient mechanical properties and thermal conductivity.

Method used

The normal pressure liquid phase sintering technology is adopted by melt deposition 3D printing. By mixing silicon carbide ceramic raw material powder, liquid phase sintering aid with dispersant, a printing material is formed, and the normal pressure liquid phase sintering is performed after layer by layer melt deposition 3D printing. The liquid phase intervention is used to significantly improve the density and uniformity of the material.

Benefits of technology

The high density and uniformity of the material are achieved, and the mechanical properties of silicon carbide ceramics such as bending strength and toughness are enhanced, while maintaining high thermal conductivity and electrical conductivity, shortening the sintering time and reducing the risk of grain growth and performance degradation caused by high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569459A_ABST
    Figure CN119569459A_ABST
Patent Text Reader

Abstract

The invention relates to fused deposition 3D printing normal pressure liquid phase sintering silicon carbide ceramic and a preparation method thereof. The preparation method of the fused deposition 3D printing normal pressure liquid phase sintered silicon carbide ceramic comprises the following steps: (1) mixing silicon carbide ceramic raw material powder, a liquid phase sintering aid and a dispersing agent to obtain primary raw material mixed powder, and then mixing the primary raw material mixed powder with an organic binder to obtain a silicon carbide ceramic printing material; (2) performing layer-by-layer fused deposition 3D printing on the silicon carbide ceramic printing material according to a designed model to obtain a silicon carbide ceramic biscuit; and (3) sequentially performing degreasing and normal-pressure liquid-phase sintering on the biscuit to obtain the fused deposition 3D printing normal-pressure liquid-phase sintered silicon carbide ceramic, the normal-pressure liquid-phase sintering process is characterized in that a degreased biscuit is placed in mixed powder of a liquid-phase sintering aid and SiC to be subjected to buried sintering treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of 3D printing of ceramic materials, and in particular relates to a fused deposition 3D printing atmospheric pressure liquid phase sintered silicon carbide ceramic and a preparation method thereof. Background Art

[0002] Silicon carbide ceramics, with its light weight, high hardness, wear resistance, thermal shock resistance, high temperature resistance, high thermal conductivity and chemical stability, play a key role in the energy, aviation, military, chemical, mechatronics and biomedical industries, especially in the semiconductor industry, it provides strong material support for the manufacture of key components such as gas separation disks and nozzles. However, the traditional ceramic preparation process has challenges such as long processing cycle and high cost, especially when manufacturing parts with complex shapes or porous structures, the limitations of these technologies are more obvious.

[0003] The rise of 3D printing technology provides a solution to these problems. It converts 3D models into a series of 2D cross-sections through CAD software and deposits materials layer by layer to build solid parts. This method not only improves manufacturing flexibility and precision, but also shortens the cycle from design to finished product and reduces costs. Among the existing 3D printing methods, the ceramic blank formed by fused deposition modeling (FDM) 3D printing has the highest solid content and low cost, so it has unique advantages in the 3D printing method of preparing silicon carbide ceramic components with complex shapes and structural mechanical strength requirements.

[0004] In addition, after using the 3D printing method to form silicon carbide ceramics with complex shapes, a densification sintering process is also required to promote further densification of the silicon carbide ceramics. The sintering methods that are more compatible with 3D printing molding mainly include reaction sintering and atmospheric pressure sintering.

[0005] Among them, reaction sintering can achieve net size sintering and form a special microstructure, but because free Si will be introduced during the sintering process, it has fatal defects in acid resistance and alkali resistance, and cannot be used in extreme environments such as high temperature; atmospheric pressure sintering can solve this problem well. It is carried out in a protective atmosphere or vacuum environment and does not require external pressure, so it is more compatible with 3D printing. However, the atmospheric pressure solid phase sintering method in atmospheric pressure sintering often cannot improve the density and uniformity of the material well, and thus cannot effectively enhance the mechanical properties of the material, such as bending strength and toughness, and cannot effectively improve the electrical conductivity and thermal conductivity of the material; in addition, atmospheric pressure solid phase sintering often has a high sintering temperature and a long sintering time, which can easily cause grain growth and material performance degradation due to high temperature. Summary of the invention

[0006] In order to realize the molding of ceramic components of complex shapes, solve the drawbacks existing in reaction sintering and achieve higher material properties, the purpose of the present invention is to provide a fused deposition 3D printing atmospheric pressure liquid phase sintering silicon carbide ceramic and its preparation method. Compared with atmospheric pressure solid phase sintering, atmospheric pressure liquid phase sintering can significantly improve the density and uniformity of the material due to the intervention of the liquid phase, thereby enhancing the mechanical properties of the material, such as bending strength and toughness, and improving the electrical conductivity and thermal conductivity of the material. In addition, the presence of the liquid phase reduces the activation energy of contact between particles, accelerates the diffusion process, and allows sintering to be completed in a shorter time. Liquid phase sintering is usually carried out at a temperature lower than that of solid phase sintering, which helps to reduce grain growth and material performance degradation caused by high temperature. These characteristics make atmospheric pressure liquid phase sintering have significant advantages in the preparation of high-performance materials.

[0007] In a first aspect, the present invention provides a method for preparing a fused deposition 3D printed atmospheric pressure liquid phase sintered silicon carbide ceramic, the preparation method comprising the following steps: (1) mixing silicon carbide ceramic raw material powder, a liquid phase sintering aid and a dispersant to obtain a primary raw material mixed powder, and then kneading the primary raw material mixed powder with an organic binder to obtain a silicon carbide ceramic printing material; (2) performing layer-by-layer melt deposition 3D printing on the silicon carbide ceramic printing material according to the designed model to obtain a silicon carbide ceramic blank; (3) degreasing and normal pressure liquid phase sintering the green blank in sequence to obtain the fused deposition 3D printed normal pressure liquid phase sintered silicon carbide ceramic; The process of normal pressure liquid phase sintering is to place the degreased green blank in a mixture of liquid phase sintering aid and SiC powder for burying and sintering.

[0008] Preferably, in step (1), the average particle size of the silicon carbide ceramic raw material powder is 0.2 to 0.8 μm, preferably 0.3 to 0.6 μm; The volume solid content of the silicon carbide ceramic printing material obtained after the mixing is 40 to 63.5 vol%, and more preferably 50 to 58 vol%.

[0009] Preferably, in step (1), based on the total mass of the silicon carbide ceramic raw material powder and the liquid-phase sintering aid as 100wt%, the mass of the silicon carbide ceramic raw material powder accounts for 90.5-95.5wt%, and the mass of the liquid-phase sintering aid accounts for 4.5-9.5wt%; the mass of the dispersant accounts for 1.25-4wt% of the total mass of the silicon carbide ceramic raw material powder and the liquid-phase sintering aid.

[0010] Preferably, in step (1), the organic binder is one of a water-based binder system, a paraffin-based binder system or an alcohol-based binder system; the amount of the organic binder used is 18.5 to 42.5 wt % of the total mass of the silicon carbide ceramic raw material powder and the liquid phase sintering aid.

[0011] Preferably, the organic binder is a paraffin-based binder system, the composition of the paraffin-based binder includes 32-48 wt% high molecular organic polymer and 52-68 wt% paraffin, and the high molecular organic polymer is at least one of polyethylene, high-density polyethylene, and polypropylene.

[0012] Preferably, in step (1), the liquid phase sintering aid is at least one of Al2O3, AlN and rare earth element oxides, preferably an Al2O3-Y2O3 mixed sintering aid; The dispersant is at least one of polyvinyl pyrrolidone, sodium tripolyphosphate, sodium lauryl sulfate, polyvinyl alcohol, polyethylene glycol, and tetramethylammonium hydroxide, preferably polyethylene glycol.

[0013] Preferably, in step (2), the process parameters of the fused deposition 3D printing include: extrusion temperature 155-185°C, extrusion nozzle diameter 0.6-1.5 mm, printing platform temperature 100-120°C, extrusion speed 10-55 mm / s, and single layer thickness 0.15-0.35 mm.

[0014] Preferably, in step (3), the degreasing includes at least one of solvent degreasing and thermal degreasing, preferably solvent degreasing is performed first and then thermal degreasing; The solvent used for the solvent degreasing is at least one of trichloroethylene, kerosene and n-heptane, the temperature of the solvent degreasing is 45-65°C, and the degreasing time is 5.5-13.5h; the temperature of the thermal degreasing is 400-1000°C, and the insulation time is 10-20h.

[0015] Preferably, in step (3), a powder-embedded atmospheric pressure liquid phase sintering process is adopted, the atmospheric pressure liquid phase sintering temperature is 1800-1950° C., the atmosphere is Ar atmosphere, and the holding time is 2-11 hours.

[0016] In a second aspect, the present invention provides a fused deposition 3D printed atmospheric pressure liquid phase sintered silicon carbide ceramic obtained according to the above preparation method, wherein the density of the fused deposition 3D printed atmospheric pressure liquid phase sintered silicon carbide ceramic is 2.79 to 3.28 g·cm -3 , preferably 2.79 to 3.18 g·cm -3 The flexural strength is 424-750 MPa, preferably 424-508 MPa, and the modulus is 384-476 GPa.

[0017] Beneficial Effects (1) Atmospheric pressure liquid phase sintering technology shows significant adaptability in combination with 3D printing technology, and effectively solves the problems existing in reaction sintering and atmospheric pressure solid phase sintering. This sintering method not only avoids the introduction of free silicon in reaction sintering, thereby preventing the defects of the material in acid resistance and alkali resistance, but also overcomes the deficiencies of atmospheric pressure solid phase sintering in density and uniformity. Atmospheric pressure liquid phase sintering significantly improves the density of silicon carbide ceramics and enhances its mechanical properties, such as flexural strength and toughness, by introducing liquid phase during the sintering process, while maintaining the high thermal conductivity and electrical conductivity of the material. In addition, the intervention of the liquid phase reduces the activation energy of contact between particles and accelerates the diffusion process, so that sintering can be completed at a lower temperature and in a shorter time, reducing the tendency of grain growth at high temperature, thereby protecting the thermal stability and microstructure of the material. (2) These advantages of atmospheric pressure liquid phase sintering technology, combined with the flexibility and design freedom of 3D printing, provide an efficient and economical solution for manufacturing complex-shaped, high-performance silicon carbide ceramic parts. This method simplifies the production process and reduces costs, while improving production flexibility. It allows sintering in a protective atmosphere or vacuum environment, ensuring precise control of the sintering environment. Ultimately, atmospheric pressure liquid phase sintering technology not only improves the performance of silicon carbide ceramics, but also broadens its application in industries such as energy, aviation, military, chemical industry, mechatronics, biomedicine, and semiconductors, providing strong material support for the manufacture of key components. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The actual object and principle schematic diagram of covering and protecting the normal pressure liquid phase sintered silicon carbide ceramic sample by using the powder embedding process in Example 1; Figure 2 The silicon carbide ceramic samples are prepared by using the powder embedding atmospheric pressure liquid phase sintering of Example 1 (left) and the atmospheric pressure liquid phase sintering of Comparative Example 1 without using the powder embedding process (right); Figure 3 The present invention uses the same binder formula and the same solid content of silicon carbide particles as raw materials for FDM printing and then undergoes normal pressure solid phase sintering and normal pressure liquid phase sintering to prepare the silicon carbide structural parts. The bending strength and modulus are compared. DETAILED DESCRIPTION

[0019] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0020] The following is an exemplary description of the preparation method of the fused deposition 3D printing atmospheric pressure liquid phase sintering silicon carbide ceramic provided by the present invention. The preparation method may include the following steps: (1) mixing silicon carbide ceramic raw material powder, liquid phase sintering aid and dispersant in a solvent, drying, crushing and sieving to obtain primary raw material mixed powder, then mixing the primary raw material mixed powder with an organic binder, and crushing to obtain silicon carbide ceramic printing material; (2) performing layer-by-layer melt deposition 3D printing on the silicon carbide ceramic printing material according to the designed model to obtain a silicon carbide ceramic blank; (3) Degreasing and normal pressure liquid phase sintering the green blank in sequence to obtain the fused deposition 3D printed normal pressure liquid phase sintered silicon carbide ceramic.

[0021] In some embodiments, in step (1), the average particle size of the silicon carbide ceramic raw material powder can be 0.2 to 0.8 μm, preferably 0.3 to 0.6 μm. In this way, it can be ensured that the raw material powder has good sintering performance and has a certain fluidity and uniformity, thereby laying the foundation for the subsequent mixing and printing steps. If the particle size is too small, the following disadvantages will occur: (1) Unsmoothness during printing: Too small a powder particle size will increase the surface area of ​​the powder, resulting in weakened fluidity of the printed material, which may cause blockage or uneven flow during extrusion, affecting the continuity and uniformity of the printed layer; (2) Agglomeration during sintering: Fine powder is prone to agglomeration during sintering, which will hinder the contact and diffusion between particles, affect the uniform densification of the material, and thus affect the performance of the finished product. Too large a particle size may cause the following disadvantages: (1) Inadequate sintering performance: Powder particles that are too large may result in insufficient contact between particles during the sintering process, reduce neck formation, and thus affect the densification of the material, which may result in a higher porosity and lower mechanical strength in the finished product; (2) Uneven microstructure: Large-particle powders may result in larger pores and an uneven microstructure inside the sintered body, affecting the uniformity and reliability of the material; (3) Increased sintering temperature: In order to achieve the same degree of densification as fine powder, large-particle powders may require a higher sintering temperature, which may result in excessively large grains and performance degradation; (4) Reduced material strength: Powders that are too large may result in reduced strength of the sintered body because larger particles may form weaker necks during the sintering process, affecting the overall strength and toughness of the material.

[0022] In some embodiments, in step (1), the liquid phase sintering aid may be at least one of Al2O3, AlN and rare earth element oxides, preferably an Al2O3-Y2O3 mixed sintering aid. The addition of the liquid phase sintering aid can promote liquid phase formation and densification during the sintering process.

[0023] The present invention adopts the Al2O3-Y2O3 liquid phase sintering aid system mainly based on the following considerations: (1) good liquid phase sintering effect: when Al2O3 and Y2O3 are mixed, a liquid phase can be formed at a relatively low temperature, thereby promoting densification during the sintering process. The formation of such a liquid phase helps to fill the gaps between the silicon carbide particles and improve the density of the sintered body; (2) excellent compatibility: Al2O3 and Y2O3 have good compatibility with SiC, and will not form a phase that is unfavorable to the silicon carbide itself or cause the material performance to deteriorate during the sintering process. Such good compatibility helps to maintain the excellent performance of silicon carbide ceramics; (3) improving thermal stability and mechanical properties: Y2O3, as a rare earth oxide, can improve the thermal stability and mechanical properties of the material. In particular, in high temperature applications, the addition of Y2O3 can improve the bending strength and fracture toughness of the material; (4) controlling grain growth: the Al2O3-Y2O3 system helps to control the grain growth during the sintering process, thereby maintaining the microstructure and performance of the material, which is crucial for maintaining the high temperature performance of silicon carbide ceramics.

[0024] Compared with other liquid-phase sintering aid systems, the unique features of the Al2O3-Y2O3 system are: (1) Lower sintering temperature: Compared with single Al2O3 or other sintering aids, the Al2O3-Y2O3 system can achieve densification at a lower temperature, thereby saving energy and reducing the degradation of material properties at high temperatures; (2) Better thermodynamic stability: The addition of Y2O3 improves the thermodynamic stability of the sintered body, making the final product more reliable for use in high-temperature environments; (3) Better microstructure control: The Al2O3-Y2O3 system helps to more finely control the microstructure of the sintered body, thereby optimizing the physical properties of the material.

[0025] In some embodiments, in step (1), the dispersant may be at least one of polyvinyl pyrrolidone (PVP), sodium tripolyphosphate (STPP), sodium dodecyl sulfate (DSS), polyvinyl alcohol (PVA), polyethylene glycol (PEG), and tetramethylammonium hydroxide (TMAH), preferably polyethylene glycol (PEG).

[0026] In some embodiments, in step (1), the solvent may be deionized water or ethanol, preferably anhydrous ethanol.

[0027] In some embodiments, in step (1), based on the total mass of the silicon carbide ceramic raw material powder and the liquid-phase sintering aid as 100wt%, the mass proportion of the silicon carbide ceramic raw material powder can be 90.5-95.5wt%, and the mass proportion of the liquid-phase sintering aid can be 4.5-9.5wt%; the mass proportion of the dispersant can be 1.25-4wt% of the total mass of the silicon carbide ceramic raw material powder and the liquid-phase sintering aid.

[0028] In the process of fused deposition 3D printing of silicon carbide ceramics, the content ratio of silicon carbide powder, binder and liquid phase sintering aid needs to be precisely controlled to ensure the fluidity of the printed material and the molding performance of the green body. The content of silicon carbide powder in the raw material is controlled within the above range to ensure sufficient solid load and good fluidity. Too high will lead to increased viscosity and affect printing continuity, while too low will reduce the strength of the molded green body. The content of liquid phase sintering aid in the raw material is controlled within the above range to ensure that sufficient liquid phase is formed during the sintering process to promote densification. Too high may lead to grain growth, while too low may affect density and mechanical properties.

[0029] In some embodiments, in step (1), the mesh size of the sieving process may be 20-100 meshes. The sieving process can ensure the fluidity and uniformity of the powder, thereby avoiding uneven printing or defects in the subsequent 3D printing process.

[0030] In some embodiments, in step (1), the organic binder can be one of a water-based binder system, a paraffin-based binder system or an alcohol-based binder system; considering the fluidity of the binder system and the subsequent non-toxic degreasing process, a paraffin-based binder system is preferred. Wherein, the composition of the paraffin-based binder can include 32-48wt% of a high molecular organic polymer and 52-68wt% of paraffin, and the high molecular organic polymer is preferably at least one of polyethylene (PE), high-density polyethylene (HDPE), and polypropylene (PP), and more preferably a mixed binder formed by polyethylene and high-density polyethylene, which is used to improve the mechanical strength and thermal stability of the binder.

[0031] Among them, the polyethylene (PE), high-density polyethylene (HDPE) and polypropylene (PP) are used as binders mainly because these polymers have excellent melt fluidity, thermal stability and mechanical strength, which can ensure the continuity of the 3D printing process and the stability of the formed blank. At the same time, they are easy to remove during the degreasing process, which helps to reduce the residual carbon during the sintering process, and are cost-effective, environmentally adaptable, and compatible with ceramic powders and liquid-phase sintering aids, thereby ensuring the uniformity of the printed material and the performance consistency of the final product.

[0032] In some embodiments, in step (1), the amount of the organic binder may be 18.5-42.5 wt% of the total mass of the silicon carbide ceramic raw material powder and the liquid phase sintering aid, to ensure extrusion performance and interlayer bonding, too much may lead to an increase in the porosity of the sintered body, and too little may lead to insufficient bonding.

[0033] In some embodiments, in step (1), the mixing process may include stirring mixing, rolling mixing, and plasticator mixing; the mixing temperature may be 140-160° C., and the mixing time may be 8-12 hours.

[0034] Mixing can improve the compatibility of powder and organic binder, thereby improving the quality of printing materials and the stability of the printing process. Crushing can ensure that the printing materials have good fluidity and plasticity, meeting the requirements of 3D printing for materials.

[0035] In some embodiments, in step (1), the volume solid content of the silicon carbide ceramic printing material obtained after mixing can be 40-63.5 vol%, preferably 50-58 vol%; in order to ensure the extrusion fluidity during the FDM printing process, the particle size range after crushing is 0.1-1.2 mm.

[0036] It should be noted that in the preparation process of fused deposition 3D printing materials, the raw material powder and the liquid phase sintering aid need to be mixed evenly first, and then mixed with the binder to form the 3D printing material. This step is crucial and has the following advantages: (1) The uniform mixing of the powder and the liquid phase sintering aid can ensure that the sintering aid is uniformly distributed in the powder, which is very critical for the subsequent sintering process. If the mixing is uneven, it may lead to incomplete sintering in local areas during the sintering process, affecting the uniformity and mechanical properties of the final material. The role of the liquid phase sintering aid is to reduce the sintering temperature and promote the densification of the material. If the powder and the sintering aid are not mixed evenly, it may lead to uneven formation of the liquid phase during the sintering process, affecting the degree of densification of the material and the final mechanical properties. (2) The addition of the binder is to improve the fluidity and molding ability of the printing material. If the powder, liquid-phase sintering aid and binder are mixed together directly, due to their differences in properties (such as density, particle size, etc.), uneven mixing may occur, resulting in defects such as holes and cracks during the 3D printing process, which will seriously affect the mechanical properties and reliability of the printed parts; (3) The uniformity of mixing directly affects the quality of the 3D printing material and the performance of the final printed parts. If the powder, sintering aid and binder are mixed together in a mixer, the slow speed of the mixer may cause uneven distribution of the binder and ultimately affect the fluidity and uniformity of the 3D printing material. Therefore, ensuring that the powder and liquid-phase sintering aid are mixed evenly before mixing with the binder is to ensure the quality of the 3D printing material and the performance of the final printed parts, and to avoid adverse effects on the 3D printing process, liquid-phase sintering and the performance of the final silicon carbide ceramic material due to uneven mixing.

[0037] In some embodiments, in step (2), the process parameters of the fused deposition 3D printing may include: extrusion temperature 155-185°C, extrusion nozzle diameter 0.6-1.5 mm, printing platform temperature 100-120°C, extrusion speed 10-55 mm / s, and single layer thickness 0.15-0.35 mm.

[0038] By precisely controlling the printing parameters, the density and quality of the ceramic blank can be ensured, and the printing parameters can be matched with the performance of the silicon carbide printing material used, thereby improving the printing performance of the material. The extrusion temperature, nozzle diameter, printing platform temperature, extrusion speed and single layer thickness jointly determine the fluidity of the printing material, the interlayer bonding strength, and the density and uniformity of the blank.

[0039] The extrusion temperature needs to be controlled at 155-185℃ to ensure the fluidity of the printed material, and 155-185℃ is compatible with the melting point of the polymer binder used in the raw material, which can ensure the melting state and fluidity of the binder during the extrusion process, and avoid the decomposition of the binder component in the raw material at too high a temperature. The nozzle diameter between 0.6 and 1.5mm can ensure the uniformity of the components in the printed layer. The maximum diameter of not more than 1.5mm can ensure the accuracy of the printed layer and the dimensional stability of the blank. The minimum diameter of not less than 0.6mm can ensure that the nozzle size is too small to cause the nozzle to be blocked or the shear stress at the nozzle is too large to cause the raw material component to segregate, providing a uniform starting material for liquid phase sintering. Maintaining the platform temperature at 100-120℃ helps interlayer bonding and ensures the strength and structural integrity of the blank. The extrusion speed in the range of 10-55mm / s ensures the uniformity of the printed layer and the density of the blank, providing a uniform density distribution for liquid phase sintering. The thickness of the single layer between 0.15 and 0.35 mm affects the porosity and interlayer composition uniformity of the final product, and corresponds to the nozzle diameter, ensuring the uniformity of the microstructure of the green body and providing a good foundation for densification during the liquid phase sintering process. The precise control of these parameters matches the performance of the silicon carbide printing raw materials, ensuring the quality of the green body and the success of the subsequent sintering process, thereby achieving the preparation of high-performance silicon carbide ceramics.

[0040] The advantages of fused deposition 3D printing (FDM) in the field of ceramic printing are mainly reflected in the simplicity of its raw material preparation, the ability to produce high-density green blanks, and the excellent mechanical properties obtained after sintering. FDM technology mixes ceramic powder with an organic binder and uses an extrusion mechanism to stack and form layer by layer. Not only is the equipment cost and operation difficulty low, but the high density of the printed green blank is also conducive to improving the structural strength after subsequent sintering. In addition, FDM technology has a high degree of design freedom and can print complex geometric shapes, including porous forms, providing greater flexibility for design. In contrast, when printing ceramic materials, selective laser 3D printing requires high-power lasers and complex post-processing processes, so the equipment cost and operation difficulty are high. In addition, the laser scanning power is high, and the thermal stress generated during rapid heating and cooling may also affect the accuracy and performance of the parts. Therefore, FDM technology has obvious advantages in cost-effectiveness, ease of operation, and the performance of printed ceramic materials.

[0041] In some embodiments, in step (2), the density of the silicon carbide ceramic blank may be 1.55 to 1.82 g·cm -3 If the density of the green billet is too small, it may weaken the bonding force between the layers, reduce the structural stability of the green billet, and lead to high porosity after sintering, which will reduce the density and strength of the material.

[0042] In some embodiments, in step (3), the degreasing may include at least one of solvent degreasing and thermal degreasing, preferably solvent degreasing is performed first and then thermal degreasing. The solvent used for the solvent degreasing may be at least one of trichloroethylene, kerosene, and n-heptane, the temperature of the solvent degreasing may be 45 to 65°C, and the degreasing time may be 5.5 to 13.5 hours; the temperature of the thermal degreasing may be 400 to 1000°C, and the insulation time may be 10 to 20 hours.

[0043] The organic binder added during the printing process can be removed by degreasing the green blank. Solvent degreasing is carried out at a certain temperature and time using a specific solvent to dissolve part of the organic binder, and the subsequent thermal degreasing is carried out at a controlled temperature to completely remove the remaining organic matter.

[0044] In some embodiments, in step (3), the atmospheric pressure liquid phase sintering can adopt the following process: the degreased green blank is placed in a mixed powder of liquid phase sintering aid and SiC for burial treatment, and then naturally cooled; the atmospheric pressure liquid phase sintering temperature can be 1800-1950°C, the atmosphere is Ar atmosphere, and the insulation time can be 2-11h.

[0045] The degreased green blank is subjected to atmospheric pressure liquid phase sintering by buried firing process, which can obtain high-density silicon carbide ceramics without external pressure; moreover, the buried firing process of the degreased green blank can inhibit the volatilization of liquid phase sintering aids. If the sintering temperature is too high, it may cause excessive grain growth and excessive volatilization of liquid phase sintering aids, affecting the microstructure and density of the material; while if the temperature is too low, sufficient liquid phase formation may not be achieved, resulting in incomplete sintering and increased porosity. If the holding time is too long, it may increase production costs and promote excessive grain growth, while if it is too short, it may lead to insufficient sintering, affecting the uniformity and densification of the material.

[0046] As an example, the following process can be used for the buried powder sintering process using Al2O3-Y2O3 liquid phase sintering aid: (1) Mixed powder laying: Since Al2O3 in the liquid-phase sintering aid is more volatile, a layer of Al2O3 powder is first laid on the bottom of the crucible as a bottom layer to provide physical support and chemical activity during the sintering process; then a layer of SiC-Al2O3-Y2O3 mixed powder is laid on the Al2O3 powder layer. The content of liquid-phase sintering aid (Al2O3-Y2O3) in the mixed powder can be twice the mass of silicon carbide powder to reduce the volatilization of the liquid-phase sintering aid and ensure the formation of the liquid phase during the sintering process; (2) Sample covering and protection: The degreased silicon carbide green blank sample to be sintered is neatly placed on the mixed powder layer, and then covered with SiC-Al2O3-Y2O3 mixed powder and Al2O3 powder as a protective layer to protect the sample and the liquid-phase sintering aid from the high temperature atmosphere and reduce the volatilization of the liquid-phase sintering aid; (3) Sintering and post-processing of samples: Graphite paper and carbon felt are placed on the top of the protective layer powder to provide good thermal conductivity and chemical stability, and then the crucible lid is tightened to ensure the sealing of the sintering environment; the sealed graphite crucible is placed in a vacuum carbon tube furnace for heating; after sintering, the sample is taken out for natural cooling, and then mechanical processing (such as grinding and polishing) is performed as needed to meet the performance and appearance requirements of the final product.

[0047] The high proportion of liquid-phase sintering aid (Al2O3-Y2O3) used in the present invention reaches twice the mass of SiC powder. The main purpose of this design is to reduce the volatilization of liquid-phase sintering aid during the sintering process. A buried firing process is formed by laying an appropriate amount of mixed powder of liquid-phase sintering aid and SiC in a crucible and covering the sintered sample with the same material. This buried firing process can effectively inhibit the volatilization of sintering aids in a high-temperature atmosphere and reduce its loss during the sintering process, thereby ensuring the stability and continuity of the liquid phase during the sintering process. The high proportion of liquid-phase sintering aid content in the buried firing process is crucial to maintaining the amount of liquid phase during the sintering process. It helps to reduce the sintering temperature, shorten the sintering time, and promote the densification of the sintered body, thereby improving the density and uniformity of silicon carbide ceramics. This uniform densification is crucial to improving the mechanical properties of the material, such as flexural strength and modulus. In addition, reducing the volatilization of the sintering aid also helps maintain the chemical composition of the sintering aid and avoids the degradation of material properties caused by incomplete reaction or volatilization of the sintering aid. Therefore, the advantage of the present invention is that it effectively reduces the volatilization of the sintering aid by accurately controlling the amount of the liquid phase sintering aid and using a high content of the liquid phase aid in the buried firing process, thereby ensuring the stability of the liquid phase during the sintering process, thereby promoting a significant improvement in the performance of the silicon carbide ceramic component.

[0048] The density of the fused deposition 3D printed atmospheric pressure liquid phase sintered silicon carbide ceramics tested by the Archimedes method is 2.79-3.28 g·cm -3 , preferably 2.79 to 3.18 g·cm -3 The flexural strength tested by the three-point flexural method is 424 to 750 MPa, preferably 424 to 508 MPa, and the modulus is 384 to 476 GPa.

[0049] In summary, the present invention ensures the excellent density and flexural strength of the final silicon carbide ceramic material through the following multiple conditions: (1) Optimized ratio of printing materials: In this patent, the ratio of silicon carbide ceramic raw material powder, liquid phase sintering aid and dispersant is precisely controlled to ensure the uniformity and fluidity of the printing materials, thereby affecting the quality of the blank and the effect of subsequent sintering; (2) Two-step degreasing process: Through the combination of solvent degreasing and thermal degreasing, this patent ensures that the organic binder is completely removed before sintering, reduces the porosity during the sintering process, and thus improves the density of the finished product; (3) Precise control of 3D printing parameters: The precise setting of extrusion temperature, nozzle diameter, printing platform temperature, extrusion speed and single layer thickness ensures the uniform deposition of the printing layer and the uniform density of the blank, providing a good foundation for subsequent sintering; (4) Normal pressure liquid phase sintering process: The liquid in this patent The phase sintering process is carried out at a lower temperature, which helps to reduce the grain growth at high temperature and improve the mechanical properties of the structural parts. At the same time, the formation of the liquid phase promotes the densification of the material, improves the density and bending strength; (5) The amount of liquid phase sintering aid: The amount of liquid phase sintering aid in this patent is twice the mass of silicon carbide powder. This unique design helps to ensure the formation of liquid phase during sintering, reduce the volatilization of the aid, and promote densification during sintering; (6) Precise control of sintering temperature and time: By sintering in the temperature range of 1800-1950℃ and the insulation time of 2-11 hours, the material is fully densified and the degradation of material properties caused by excessive sintering is avoided; (7) Sintering under protective atmosphere: Sintering in Ar atmosphere prevents material oxidation, provides good thermal conductivity and chemical stability, and helps the uniformity of liquid phase sintering. Through the combined effect of the above conditions, it is ensured that without the impregnation heat treatment and other processes, a high density (2.79-3.28g·cm) is successfully prepared. -3 ) and high flexural strength (440-750MPa) silicon carbide ceramic.

[0050] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values ​​​​exemplified below. If not specifically stated, the technical means used in the embodiments are conventional means well known to those skilled in the art.

[0051] Example 1

[0052] The preparation method of fused deposition 3D printing atmospheric pressure liquid phase sintering silicon carbide ceramics provided in this embodiment includes the following steps: (1) Preparation of silicon carbide ceramic printing material: 93.00 wt% of silicon carbide ceramic powder with an average particle size of 0.5 μm, 3.2 wt% of Al2O3, and 3.8 wt% of Y2O3 were added in proportion to prepare an inorganic powder, and 3 wt% of the total mass of the inorganic powder was added to the dispersant polyethylene glycol (PEG); alcohol was used as a solvent, mixed at a speed of 105 rpm for 12 h, and then mixed in the opposite direction for 12 h to obtain a uniformly mixed liquid slurry; the obtained mixed slurry was placed in an oven and dried at a temperature of 70°C, crushed by a crusher, and sieved to obtain a uniformly dispersed primary raw material mixed powder; then, the primary raw material mixed powder was preheated and mixed with an organic binder, wherein the binder component contained 20 wt% PE, 20 wt% HDPE and 60 wt% PW, and crushed to obtain a silicon carbide ceramic printing material with an average particle size of 0.8 mm. (2) Preparation of silicon carbide ceramic blank: Put silicon carbide ceramic printing material into the printing equipment, adopt the fused deposition 3D printing method, and print the silicon carbide ceramic blank with complex shape layer by layer according to the designed model; set the printing parameters as follows: extrusion temperature 175°C, extrusion nozzle diameter 0.8mm, printing platform temperature 110°C, extrusion speed 35mm / s, single layer thickness 0.25mm; the density of the silicon carbide ceramic blank is 1.82g·cm -3 . (3) Degreasing and densification: The printed blank is placed in trichloroethylene for solvent degreasing, and then placed in a water bath for constant temperature heating. The temperature is set to 60°C and the degreasing time is 11 hours. After taking it out, it is placed in an oven for drying at 80°C for 6 hours. After solvent degreasing, it is placed in a vacuum sintering furnace for thermal degreasing. The thermal degreasing temperature is 800°C and the holding time is 11 hours. Then, Al2O3 powder is laid on the bottom of the crucible, and then SiC-Al2O3-Y2O3 mixed powder is laid, and the amount of liquid phase sintering aid is controlled to be twice the mass of silicon carbide powder; the silicon carbide sample is placed on the mixed powder, and then covered with the mixed powder and Al2O3 powder, graphite paper and carbon felt are placed on the upper layer of the powder, and after tightening the crucible lid, the crucible is placed in a vacuum carbon tube furnace for heating, the sintering temperature is set to 1900°C, and kept warm for 6 hours in an Ar atmosphere to obtain the fused deposition 3D printed atmospheric pressure liquid phase sintered silicon carbide ceramics.

[0053] After testing, the density of the fused deposition 3D printed atmospheric pressure liquid phase sintered silicon carbide ceramic sample prepared in this embodiment is 3.15 g·cm -3 , the flexural strength is 508MPa and the modulus is 476GPa.

[0054] Figure 1The figure and principle diagram of the protective covering of the pressureless liquid phase sintered silicon carbide ceramic sample by the powder embedding process in Example 1.

[0055] Example 2

[0056] The preparation method of the fused deposition 3D printing atmospheric pressure liquid phase sintering silicon carbide ceramic provided in this embodiment refers to Example 1, with the main differences being: In step (1), the average particle size of silicon carbide ceramic powder is 0.8 μm, and the liquid phase sintering aid is 3.2 wt% AlN and 3.8 wt% rare earth element oxide (Re2O3) to prepare inorganic powder, and 1.5 wt% of the total mass of the inorganic powder is added as dispersant polyvinyl pyrrolidone (PVP); In step (3), the degreased green blank is subjected to a high-temperature sintering process, wherein the temperature of normal pressure liquid phase sintering is set to 1800°C.

[0057] After testing, the density of the fused deposition 3D printed atmospheric pressure liquid phase sintered silicon carbide ceramic sample prepared in this embodiment is 3.08 g·cm -3 , the flexural strength is 459MPa and the modulus is 410GPa.

[0058] Comparative Example 1

[0059] The preparation method of the silicon carbide ceramic provided in this comparative example refers to Example 1, with the main differences being: In step (3), the buried firing process is not adopted, but the degreased silicon carbide blank is directly placed in a crucible for normal pressure liquid phase sintering.

[0060] After testing, the silicon carbide ceramic sample prepared in this comparative example has a density of 2.91 g·cm -3 , the flexural strength is 405MPa and the modulus is 382GPa.

[0061] Figure 2 The silicon carbide ceramic samples are prepared by the powder-embedded atmospheric pressure liquid phase sintering of Example 1 (left) and the normal pressure liquid phase sintering without the powder-embedded process of Comparative Example 1 (right). It can be seen from the figure that the silicon carbide sample sintered without the powder-embedded process has a large dimensional deformation and has defects such as cracks and delamination in the cross section.

[0062] Comparative Example 2

[0063] The preparation method of the silicon carbide ceramic provided in this comparative example refers to Example 1, with the main differences being: In step (1), 96.50 wt% of 0.5 μm silicon carbide ceramic powder is used, and 0.50 wt% of boron carbide and 3 wt% of carbon black are used as solid phase sintering aids; In step (3), a solid phase sintering temperature of 2100° C. is adopted.

[0064] After testing, the silicon carbide ceramic sample prepared in this comparative example has a density of 2.98 g·cm -3 , the flexural strength is 365MPa and the modulus is 339GPa.

[0065] Figure 3 The bending strength and modulus of silicon carbide structural parts prepared by FDM printing with silicon carbide particles of the same binder formula and the same solid content and then subjected to pressureless solid phase sintering and pressureless liquid phase sintering are compared. As can be seen from the figure, the average bending strength and modulus of the samples sintered by pressureless liquid phase are increased by 27.7% and 24.6% respectively compared with those sintered by pressureless solid phase.

[0066] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for preparing fused deposition 3D printing atmospheric pressure liquid phase sintered silicon carbide ceramics, characterized in that: The preparation method comprises the following steps: (1) mixing silicon carbide ceramic raw material powder, a liquid phase sintering aid and a dispersant to obtain a primary raw material mixed powder, and then kneading the primary raw material mixed powder with an organic binder to obtain a silicon carbide ceramic printing material; (2) performing layer-by-layer melt deposition 3D printing on the silicon carbide ceramic printing material according to the designed model to obtain a silicon carbide ceramic blank; (3) degreasing and normal pressure liquid phase sintering the green blank in sequence to obtain the fused deposition 3D printed normal pressure liquid phase sintered silicon carbide ceramic; The process of normal pressure liquid phase sintering is to place the degreased green blank in a mixture of liquid phase sintering aid and SiC powder for burying and sintering.

2. The preparation method according to claim 1, characterized in that: In step (1), the average particle size of the silicon carbide ceramic raw material powder is 0.2 to 0.8 μm, preferably 0.3 to 0.6 μm; The volume solid content of the silicon carbide ceramic printing material obtained after the mixing is 40 to 63.5 vol%, and more preferably 50 to 58 vol%.

3. The preparation method according to claim 1 or 2, characterized in that: In step (1), taking the total mass of silicon carbide ceramic raw material powder and liquid-phase sintering aid as 100wt%, the mass proportion of silicon carbide ceramic raw material powder is 90.5-95.5wt%, the mass proportion of liquid-phase sintering aid is 4.5-9.5wt%; the mass proportion of dispersant is 1.25-4wt% of the total mass of silicon carbide ceramic raw material powder and liquid-phase sintering aid.

4. The preparation method according to any one of claims 1 to 3, characterized in that In step (1), the organic binder is one of a water-based binder system, a paraffin-based binder system or an alcohol-based binder system; the amount of the organic binder used is 18.5 to 42.5 wt % of the total mass of the silicon carbide ceramic raw material powder and the liquid phase sintering aid.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The organic binder is a paraffin-based binder system, and the composition of the paraffin-based binder includes 32-48 wt% of high molecular organic polymer and 52-68 wt% of paraffin. The high molecular organic polymer is at least one of polyethylene, high-density polyethylene, and polypropylene.

6. The preparation method according to any one of claims 1 to 5, characterized in that: In step (1), the liquid phase sintering aid is at least one of Al2O3, AlN and rare earth element oxides, preferably an Al2O3-Y2O3 mixed sintering aid; The dispersant is at least one of polyvinyl pyrrolidone, sodium tripolyphosphate, sodium lauryl sulfate, polyvinyl alcohol, polyethylene glycol, and tetramethylammonium hydroxide, preferably polyethylene glycol.

7. The preparation method according to any one of claims 1 to 6, characterized in that In step (2), the process parameters of the fused deposition 3D printing include: extrusion temperature 155-185°C, extrusion nozzle diameter 0.6-1.5 mm, printing platform temperature 100-120°C, extrusion speed 10-55 mm / s, and single layer thickness 0.15-0.35 mm.

8. The preparation method according to any one of claims 1 to 7, characterized in that: In step (3), the degreasing includes at least one of solvent degreasing and thermal degreasing, preferably solvent degreasing is performed first and then thermal degreasing; The solvent used for the solvent degreasing is at least one of trichloroethylene, kerosene and n-heptane, the temperature of the solvent degreasing is 45-65°C, and the degreasing time is 5.5-13.5h; the temperature of the thermal degreasing is 400-1000°C, and the insulation time is 10-20h.

9. The preparation method according to any one of claims 1 to 8, characterized in that: In step (3), a powder-embedded atmospheric pressure liquid phase sintering process is adopted, the atmospheric pressure liquid phase sintering temperature is 1800-1950° C., the atmosphere is Ar atmosphere, and the holding time is 2-11 hours.

10. A fused deposition 3D printing atmospheric pressure liquid phase sintered silicon carbide ceramic obtained by the preparation method according to any one of claims 1 to 9, characterized in that: The density of the fused deposition 3D printed atmospheric pressure liquid phase sintered silicon carbide ceramic is 2.79 to 3.28 g cm -3 , preferably 2.79 to 3.18 g·cm -3 The flexural strength is 424-750 MPa, preferably 424-508 MPa, and the modulus is 384-476 GPa.

Citation Information

Patent Citations

  • Full 3D printing silicon carbide ceramic optical component and preparation method thereof

    CN115724663A

  • Method for preparing SiC ceramic by combining selective laser 3D printing / precursor dipping pyrolysis / liquid phase sintering

    CN116675538A